2021
DOI: 10.1111/cid.13033
|View full text |Cite
|
Sign up to set email alerts
|

Geometric accuracy of magnetic resonance imagingderived virtual 3‐dimensional bone surface models of the mandible in comparison to computed tomography and cone beam computed tomography: A porcine cadaver study

Abstract: Background: Providing accurate 3-dimensional virtual bone surface models is a prerequisite for virtual surgical planning and additive manufacturing in craniomaxillofacial surgery. For this purpose, magnetic resonance imaging (MRI) may be a radiation-free alternative to computed tomography (CT) and cone beam computed tomography (CBCT).Purpose: The aim of this study was to assess the geometric accuracy of 3-dimensional T1-weighted MRI-derived virtual bone surface models of the mandible in comparison to CT and CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Numerous studies have compared the differences between two 3-dimensional models using RMSE values. 16,20,27,32 The 3-dimensional shape of the required implanted bone block and bone harvesting site were also designed for the control group and provided to the surgeon for reference. This might provide more guidance to surgeons than the routine imaging data, thereby improving surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have compared the differences between two 3-dimensional models using RMSE values. 16,20,27,32 The 3-dimensional shape of the required implanted bone block and bone harvesting site were also designed for the control group and provided to the surgeon for reference. This might provide more guidance to surgeons than the routine imaging data, thereby improving surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the RMSE values in the guide and control groups were 0.37 ± 0.16 and 0.72 ± 0.29 mm ( p < 0.001), respectively, indicating that using the combination of guides could improve the predictability and outcomes of the block bone grafting procedure as compared to the conventional free‐hand surgery. Numerous studies have compared the differences between two 3‐dimensional models using RMSE values 16,20,27,32 . The 3‐dimensional shape of the required implanted bone block and bone harvesting site were also designed for the control group and provided to the surgeon for reference.…”
Section: Discussionmentioning
confidence: 99%
“…No additional hardware or specific software is needed to acquire and interpret the images. Furthermore, the geometric accuracy of the deployed 3D T1 GRE sequence compared to CT and CBCT has been shown before [ 23 ]. Furthermore, MRI does not only give information about the osseous anatomy but at the same time acquires information regarding trauma to the surrounding soft tissue.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Van der Cruyssen et al and Juerchott et al have shown that by optimizing sequence protocols, direct visualization of small trigeminal branches and even complex structures like the dental pulp is possible, which improves our understanding of nerve physiology in vivo [36][37][38][39]. Furthermore, using T1-based imaging or ultrashort or zero echo time sequences, even the visualization of hard tissues like the mandibular bone and pathological alterations in the course of periodontitis or osteonecrosis has been feasible [9,27,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In periodontics, Probst et al described water-sensitive STIR sequences to detect bone edema in generalized periodontitis, and Juerchott et al described the use of MRI for the evaluation of furcation defects [9,19]. In oral surgery, the use of MRI for implant planning and third molar removal demonstrated good diagnostic accuracy [27][28][29]. In orthodontics, a recent MRI study showed reliable 3D cephalometric analysis when compared to CBCT [30].…”
Section: Introductionmentioning
confidence: 99%